2022
DOI: 10.3390/antibiotics11020244
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Antibiotic Use in Zimbabwe in the COVID-19 Era: A Perfect Recipe for Antimicrobial Resistance

Abstract: The global COVID-19 pandemic has resulted in an upsurge in antimicrobial use. The increase in use is multifactorial, and is particularly related to the empirical treatment of SARS-CoV-2 and suspected coinfections with antimicrobials and the limited quality of diagnostics to differentiate viral and bacterial pneumonia. The lack of clear clinical guidelines across a wide range of settings, and the inadequacy of public health sectors in many countries, have contributed to this pattern. The increased use of antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(53 reference statements)
0
17
1
1
Order By: Relevance
“…An interview-based study in Nigeria reported up to a 6-fold increase in antibiotic use among local pharmacists during the first wave of COVID-19 in 2020 ( 37 ). There have been reports concerning the inappropriate and increased use of antibiotics during the COVID-19 pandemic in low- and middle-income countries, such as Zimbabwe ( 38 ), Malawi, and Uganda ( 39 ). This includes antibiotics used in the hospital and at home (over-the-counter drugs without a prescription).…”
Section: Discussionmentioning
confidence: 99%
“…An interview-based study in Nigeria reported up to a 6-fold increase in antibiotic use among local pharmacists during the first wave of COVID-19 in 2020 ( 37 ). There have been reports concerning the inappropriate and increased use of antibiotics during the COVID-19 pandemic in low- and middle-income countries, such as Zimbabwe ( 38 ), Malawi, and Uganda ( 39 ). This includes antibiotics used in the hospital and at home (over-the-counter drugs without a prescription).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chitungo et al stated that the COVID-19 pandemic has led to extensive use of antibiotics due to the lack of knowledge about the disease at the early stages of the pandemic. They concluded that such inappropriate use of antibiotics during COVID-19 has intensified the risk of antimicrobial resistance (AMR) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“… 39 Countries should be closely tracking the use of antibiotics amid the COVID-19 pandemic and training health workers on antimicrobial stewardship. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%